Organised crime and law enforcement : a network perspective / David Bright and Chad Whelan. - Bright, David (David A.); Whelan, Chad (Routledge studies in organised crime., 2021)
"Organised Crime and Law Enforcement: A Network Perspective examines organised crime and law enforcement through the conceptual lens of networks. The book takes stock of the many ways in which network theories and concepts, including social network analysis, can apply to studying both organised crime and law enforcement responses to organised crime. It is the first attempt to bring these diverse network perspectives and distinct fields of research together. The book is organised into two parts. The first part uses network perspectives to advance our understanding of the interconnected social structure of organised criminal groups, to expose their strengths and vulnerabilities, and to illuminate factors that enable such groups to undertake complex criminal activities. The second part uses a network lens to examine the challenges that organised criminal groups present for a wide range of law enforcement agencies, and the utility of network theories and concepts in understanding and informing their responses to organised crime. Written in a clear and direct style, the book will appeal to scholars and practitioners of criminology, sociology, law enforcement and all those interested in learning more about theories of organised crime and its relationship with law enforcement"--